Lectotype selection for Aedes quasirustius (Diptera: Culicidae) - Reinert, John F. (European Mosquito Bulletin, 1999)
A lectotype is selected from syntype specimens of Aedes quasirusticus Canamares. Condition and label data of the lectotype are provided.